2017
DOI: 10.15406/jbmoa.2017.04.00092
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Characterization of Some Bacteria from Soil Samples of Agbaja Iron Ore Mining Site of Kogi State

Abstract: Hydrometallurgical and other conventional mining technologies on low grade ores require high energy and capital costs. The use of microbes to degrade such type of minerals is gaining acceptance. This study was carried out, therefore to isolate, identify and characterize iron solubilizing bacteria from Iron stones of Agbaja iron ore mining site of Kogi State. Crushed samples in the range of 0.25µm and 0.75µm particle size were used for the isolation. They were cultured in a modified 9k media to facilitate bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In contrast to the findings obtained in this study, Margesin et al [ 41 ] reported larger counts of cultivable bacterial communities in heavily contaminated soil polluted by heavy metals. Other studies by Emmanuel et al [ 42 ] reported a lower bacterial count (12.3 × 10 3 cfu/g) in the soil of mining sites in Nigeria.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast to the findings obtained in this study, Margesin et al [ 41 ] reported larger counts of cultivable bacterial communities in heavily contaminated soil polluted by heavy metals. Other studies by Emmanuel et al [ 42 ] reported a lower bacterial count (12.3 × 10 3 cfu/g) in the soil of mining sites in Nigeria.…”
Section: Discussionmentioning
confidence: 87%
“…The heavy metal–tolerant isolates recovered were Gram negative, which studies [ 42 , 43 ] showed to be more tolerant to heavy metals than Gram positive. This attribute could be due to the interaction between the bacterial cell wall and the metal ions on the surface and the interface of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Ten heavy metal-tolerant isolates were recovered of which preliminary identification analysis revealed five to be Gram-positive while the other five were Gram-negative. Interestingly, studies have shown that Gram-negative bacteria are more tolerant to heavy metals than Gram-positive bacteria, a phenomenon which has been suspected to be due to the ability of their cell wall to interact with the metal ions on the surface and the interface of the bacteria [28,46]. Further subjection of the bacteria isolates to minimum inhibitory concentration tests revealed isolates 2, 6, 7, and 9 as the isolates capable of tolerating high concentrations of Pb, Co, Cd, Zn, and Hg as evident in Table 9.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological characteristics of the bacteria colonies such as edges, shape, and surface were observed and recorded [28]. The identification and characterization of bacteria isolates were performed by carrying out grams staining and other relevant biochemical tests which include catalase test, coagulase test, indole production test, citrate utilization test, and sugar fermentation [29,30].…”
Section: Characterization Of Bacterial Isolatesmentioning
confidence: 99%